Benign Vulvar Adnexal Tumours - A 5 Year Study in a Tertiary Care Hospital - Kanwardeep Kaur Tiwana; Sarita Nibhoria; Harpreet Kaur; Akanksha Bajaj; Richa Phutela (Tehran University of Medical Sciences, 2016)
Despite of the fact that the vulva contains a high density of apocrine and anogenital mammary glands in addition to eccrine glands and folliculosebaceous units, the benign vulvar adnexal tumours are rare. Though the varied clinical presentation and diverse histopathological spectrum of vulvar neoplasms has amazed the pathologists, only few studies have been reported in literature. The present five year study consists of only five cases of benign vulvar neoplasms depicting their rarity. Hidradenoma papilliferum and syringoma were the most common entities followed by Chondroid syringoma. The aim of our study is to explore and highlight the histopathological diversity of benign vulvar adnexal tumours reflecting the relative frequency of these structures.